2021
DOI: 10.3390/jpm11050416
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Respiratory Syncytial Virus in Children under 5 Years of Age in the WHO European Region: A Systematic Review and Meta-Analysis

Abstract: A respiratory syncytial virus (RSV) is the major cause of respiratory tract infection in children under 5 years. However, RSV infection in the European Region of the World Health Organization has not been systematically reviewed. The aim was to determine the prevalence and factors associated with RSV in children under 5 years of age in European regions. A systematic review and meta-analysis was performed. CINAHL, Medline, LILACS, ProQuest, SciELO, and Scopus databases were consulted for studies published in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
3
16
0
6
Order By: Relevance
“…RSV seasonality in our study was consistently observed during the cold fall-winter months of November–March, in agreement with prior reports [ 4 , 32 , 36 , 41 , 51 54 ]. Multiple meteorological factors were shown to be associated with RSV incidence rates and activity [ 53 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…RSV seasonality in our study was consistently observed during the cold fall-winter months of November–March, in agreement with prior reports [ 4 , 32 , 36 , 41 , 51 54 ]. Multiple meteorological factors were shown to be associated with RSV incidence rates and activity [ 53 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Respiratory syncytial virus (RSV) is a main cause of acute bronchiolitis [ 1 ], and pneumonia in infants and young children [ 2 , 3 ]. Usually the incidence of RSV bronchiolitis displays a seasonal pattern, during the cold (winter) months in regions with temperate climates [ 4 ]. Globally, the highest incidence of severe RSV lower respiratory tract infection was reported among children aged less than 6 months [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our series, gender resulted in not being a risk factor for hRSV infection; a similar result was reported by Pellegrinelli et al [31] in children up to 5 years of age presenting ILI symptoms, whereas Grunberg et al [32] highlighted a significant higher prevalence of hRSV infections in females. Nevertheless, there is still ambiguity in the global epidemiological data regarding gender [33], and sex differences in respiratory viral pathogenesis have also been hypothesized, with males more susceptible to severe outcomes from respiratory viral infections at younger and older ages [34].…”
Section: Discussionmentioning
confidence: 99%
“…As it is known, the highest risk age group susceptible to viral infection are infants, the elderly, and immunocompromised people [25][26][27][28]. However, during pregnancy, the women increase their probability of having complications from a respiratory viral infection, such as preeclampsia, acute cardiopulmonary diseases, respiratory distress, and pneumonia, among others [29,30].…”
Section: Hrsv Infection During Pregnancy and Effects On The Newbornmentioning
confidence: 99%